Queer Catrumana Cartography: A Study on Lgbtqiapn+ lives in the North of Minas Gerais (Revista Espinhaço, 2024)
This article seeks to carry out a queer cartography of LGBTQIAPN+ subjectivities in the North of Minas Gerais. To this end, we chose to analyze the scientific productions on this theme and understand how the academic discourse has recorded these ways of life, experiences and (re)existences and produced them as identities. In all, 33 productions were selected (including articles, chapters, annals, dissertations and theses). Thus, it was based on the theorizations of Paul Preciado, Jack Halberstam, Teresa de Lauretis, Judith Butler and Michel Foucault. There is a scarcity of productions on this theme, configuring itself as a discursive interdiction; in addition to the mechanisms triggered by LGBTphobia and cisheteronormativity in the studied region; the conflicts between public and private space; and assimilationism. The selected writings were grouped in three central categories, basing on their discussions: the trajectories and mobilizations of the LGBTQIAPN+ community, the public space experiences, and the dialogues that were established with local politics and educational experiences. However, we highlight the short amount of works, which reveals a lack of research on dissident lives in the north of Minas Gerais. Furthermore, the majority of writings are restricted to the experiences in the city of Montes Claros, even though we sought out to study the whole region. Ultimately, it’s evident the maintenance of a cishetonormative and violent regime, which operates not only on the materiality of the bodies, but also in the documentation of this violence, silencing and making invisible these existences.
Keywords: Queer Cartography; North of Minas Gerais; LGBTQIAPN